The incidence and variation of corona mortis in multiracial Asian: an insight from 82 cadavers - Khirul-Ashar, N.A.; Ismail, I.I.; Hussin, P.; Nizlan, N.M.; Harun, M.H.; Mawardi, M.; Lingam, R. (Malaysian Orthopaedic Association, 2024)
Introduction: Corona Mortis (CMOR) is a term used to describe an anatomical vascular variant of retropubic anastomosis located posterior to superior pubic ramus. We aim to provide sufficient data on the incidence, morphology and mean location of ‘crown of death’ in Asian population. Other objectives include to assess the relationship between CMOR incidence with gender, race and age. Materials and methods: This is a cross-sectional cadaveric study involving 164 randomly selected fresh multiracial Asian hemipelves (82 cadavers). Hemipelves were dissected to expose and evaluate the vascular elements posterior to superior pubic rami. Data were analysed using Chi-Square, t-test and with the help of IBM SPSS Statistics v26 software. Results: CMOR was found in 117 hemipelves (71.3%). No new morphological subtype was found. The mean distance of CMOR to symphysis pubis was 54.72mm (SD 9.35). Based on the results, it is evident that precaution needed to be taken at least within 55mm from symphysis pubis during any surgical intervention. The lack of statistically significant correlation between CMOR occurrence and gender, race and age suggest that the incidence of CMOR could be sporadic in manner. Conclusion: We conclude that CMOR is not just aberrant vessel as the incidence is high and this finding is comparable to other studies. The mean location of CMOR obtained in this study will guide surgeons from various disciplines in Asia to manage traumatic vascular injury and to perform a safe surgical procedure involving the pelvis area.